PENGARUH KOMUNIKASI INTERPERSONAL DAN STRES KERJA TERHADAP KOMITMEN ORGANISASI PEGAWAI PUSDIKLAT BEA DAN CUKAI - Rita Dwi Lindawati (Jurnal Manajemen Pendidikan, 2014)
The objective of the research is to know the effect of interpersonal communication and job stress on organizational commitment on employee. This research used quantitative approach. The research was conducted of Customs and Excise Training Center by using a survey method with path analysis applied in testing hypothesis. The number of 50 employee as sample was selected by using Slovin formula. The research conclude: (1) There is a direct positive effect of interpersonal communication on organizational commitment (2) There is a direct negative effect of work stress on commitment organization (3) There is a direct negative effect of interpersonal communication on organizational commitment.